The Effect of Corporate Social Responsibility on Firm Value with Intellectual Capital as a Moderating Variable - Editha Pramesti; Rino Tam Cahyadi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2026)
This study entitled The Effect of Corporate Social Responsibility on Firm Value with Intellectual Capital as a Moderating Variable aims to examine the effect of Corporate Social Responsibility on firm value and investigate whether intellectual capital moderates this relationship. The research was motivated by inconsistent findings in previous studies and the growing importance of sustainable business practices in the Indonesian financial sector. A quantitative approach was employed using panel data regression analysis on 26 financial sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period, resulting in 130 observations. Firm value was measured using Tobin's Q, Corporate Social Responsibility was measured using the Corporate Social Responsibility disclosure score, and intellectual capital was measured using the Value Added Intellectual Coefficient. The findings indicate that Corporate Social Responsibility has a positive and significant effect on firm value, suggesting that greater sustainability disclosure enhances stakeholder trust, corporate reputation, and market valuation. However, intellectual capital was not found to significantly moderate the relationship between Corporate Social Responsibility and firm value. These findings highlight the strategic importance of Corporate Social Responsibility in creating long-term corporate value while suggesting that intellectual capital contributes through a different mechanism.